AVALIAÇÃO DA RESPOSTA À VACINA BRASILEIRA CONTRA HEPATITE B (BUTANG®) EM RECÉM-NASCIDOS EM GOIÂNIA, GOIÁS - TAVARES, Viviane Rodrigues (2009)
Hepatitis B vaccination is the major mode of hepatitis B prevention. To evaluate the immunogenicity and reactogenicity of the Brazilian hepatitis B vaccine (Butang®) in newborns in Goiania-GO, 294 infants born in the east of Goiânia, Goiás, were recruited. All of them received the first vaccine dose in the first 12 hours of life. The second and third doses were applied 30 and 150 days after, respectively. About 45 days after the last dose, blood samples were collected from 250 children in order to detect quantitative anti-HBs, using the enzyme immunoassay of microparticles (MEIA). All participants were evaluated 48-72 hours after each dose to investigate local and systemic reactions. Mothers of newborns were screened for anti-HBs and anti-HBc by enzyme immunoassay. Of 250 newborns who completed the study, 97.6% (95% CI: 94.8-99.1) developed anti-HBs protector titers, being most of them higher than 100 mIU/mL (90,8%). The anti-HBs geometric mean titer was equal to 572 mIU/mL (95% CI: 471.1 - 694.6), and no difference was observed between female and male newborns. Low responders NB (10-99 mIU/ml) were more frequent in male infants (58,8% vs 41,2%). Maternal anti-HBs and/or anti-HBc-positivity did not interfere in the newborns vaccine response. Concerning reactogenicity, only induration (5.5%), redness (2.4%), heat (1.3%) and fever (12.9%) were observed following the 829 vaccine doses applied. Six newborns did not respond to Butang® vaccine. Of them, four were male. A booster dose was applied in all no vaccine responders. All but one not developed anti-HBs protector titers following a booster dose. The Butang® showed to be safe and immunogenic when administered to newborns in the first 12 hours of life. However, more studies will be need to evaluate its lifetime effectiveness.